Роль малого бізнесу в регіональній економіці - Соколенко, Володимир Анатолійович; Струкова, А. Г. (НТУ "ХПІ", 2013)
Formulated advantages of small business versus big business, the present condition of small business sector in the regions of Ukraine, studied international experience of its establishment and operation, describes the heterogeneity of Ukraine in the economic and socio-political terms as the cause of inefficient state support of small business.
Keywords: підприємництво; економіка; підтримка державна